(untitled) (Studia theodisca, 2012)
Thomas Mann is an author without a fixed point of view. When he discusses a problem he tends to opt for an «on the one hand – on the other hand». His novella Wälsungenblut is the epitome of aestheticism. How is this aestheticism portrayed? For once the author appears to be unfaithful to his typical way of thinking and to give way to satire. One of the most interesting aspects is how Richard Wagner’s Walküre is included in this argument.